Can facility-based transitional care improve patient flow? Lessons from four Canadian regions. Issue 3 (May 2021) - Kreindler, Sara A.; Struthers, Ashley; Star, Noah; Bowen, Sarah; Hastings, Stephanie; Winters, Shannon; Johnson, Keir; Mallinson, Sara; Brierley, Meaghan; Anwar, Mohammed Rashidul; Aboud, Zaid; Basran, Jenny; et al.
Units providing transitional, subacute, or restorative care represent a common intervention to facilitate patient flow and improve outcomes for lower acuity (often older) inpatients; however, little is known about Canadian health systems' experiences with such "transition units." This comparative case study of diverse units in four health regions (48 interviews) identified important success factors and pitfalls. A fundamental requirement for success is to clearly define the unit's intended population and design the model around its needs. Planners must also ensure that the unit be resourced and staffed to deliver truly restorative care. Finally, streamlined processes must be developed to help patients access and move through the unit. Units that were perceived as more effective appeared to have satisfactorily addressed these population, capacity, and process issues, whereas those perceived as less effective continued to struggle with them. Findings suggest principles to support optimal design and implementation of transition units.